Targeting feasibility evaluation of magnetic resonance-guided focused ultrasound in the management of osteomyelitis: a virtual treatment planning study in 75 patients - Amanda Beserra; Samuel Pichardo; David Kisselgoff; Valentina Peeva; Laura Curiel (International Journal of Hyperthermia, 2019)
Purpose: Osteomyelitis is one of the most serious complications linked to diabetes and increases the possibility of limb amputation considerably. There exists an important clinical need to improve management of osteomyelitis, especially for diabetic patients who are more susceptible to failures, relapses and chronicity of multiple bone infections. Magnetic resonance-guided focused ultrasound (MRgFUS) can offer a clinical management option for patients with osteomyelitis by providing a non-surgical and potentially rapid-recovery treatment option. Material and Methods: A retrospective study with patients with confirmed osteomyelitis (n = 75) was performed at evaluating the feasibility to target bone infection sites with a clinically approved MRgFUS device (Sonalleve, Profound Medical, Mississauga, ON, Canada). The developed methodology allows using preexisting diagnostic magnetic resonance imaging (MRI) or computed tomography (CT) scans to evaluate the treatment feasibility directly using a MRgFUS treatment planning software. Results: 74.7% of the cases included in our study passed the targetability criteria. Cases were deemed non-targetable if the target was less than 1 cm from the skin or close to a neuro-vascular bundle, metallic implants, or in the way of a defect in the overlying skin. For cases that passed the targetability criteria, an average among patients of 92.7 ± 5.2% of the gross treatment volume could be reached using treatment cells available at the Sonalleve system. Conclusion: The retrospective study presented here is the first step to demonstrate the feasibility of utilizing MRgFUS for the thermal treatment of osteomyelitis.